"Insta-Mother Care": The Impact of Micro-Counseling via Instagram Reels on Pregnant Women's Self-Care Behavior - Latifah Latifah; Dwi Rahmawati; Chynthia Eka Fayuning Tjomiadi; M. Sobirin Mohtar; Siti Aisyah; Rizky Puteri Anggraini (Indonesian Journal of Global Health Research, 2025)
Limited access to adequate health education and support is a major challenge in improving self-care behaviors among pregnant women. Social media, specifically Instagram Reels, has the potential to be an innovative, affordable, and accessible micro-counseling platform to address this gap. This study aims to analyze the effectiveness of micro-counseling through Instagram Reels in improving pregnant women's self-care knowledge and behaviors, and to identify challenges and opportunities for its implementation. This quasi-experimental study with a pretest-posttest control group design involved 30 pregnant women in Banjarmasin City, selected using a purposive sampling technique. The sample was then divided into an intervention group and a control group. The intervention group received a micro-counseling intervention through Instagram Reels (@instamothercare) for 4 weeks, containing educational content on nutrition, exercise, stress management, and childbirth preparation. Data were collected using a questionnaire on knowledge, self-care behaviors, and the Edinburgh Depression Scale, and analyzed using Mann-Whitney test. The Mann-Whitney test results showed in knowledge scores between the control and intervention groups a p value = 0.511, behavior scores between the control and intervention groups 0.154, and mental health scores between the control and intervention groups 0.216. There was no statistically significant difference in knowledge scores between the control and intervention groups. There was no statistically significant difference in behavior scores between the control and intervention groups. And there was no statistically significant difference in mental health scores between the control and intervention groups.